AdS3 solutions in massive IIA with small N $$ \mathcal{N} $$ = (4, 0) supersymmetry - Yolanda Lozano; Niall T. Macpherson; Carlos Nunez; Anayeli Ramirez (Journal of High Energy Physics)
Abstract We study AdS3 x S 2 solutions in massive IIA that preserve small N $$ \mathcal{N} $$ = (4, 0) supersymmetry in terms of an SU(2)-structure on the remaining internal space. We find two new classes of solutions that are warped products of the form AdS3 x S2 x M4 x ℝ. For the first, M4=CY2 and we find a generalisation of a D4-D8 system involving possible additional branes. For the second, M4 need only be Kahler, and we find a generalisation of the T-dual of solutions based on D3-branes wrapping curves in the base of an elliptically fibered Calabi-Yau 3-fold. Within these classes we find many new locally compact solutions that are foliations of AdS3 x S2 x CY2 over an interval, bounded by various D brane and O plane behaviours. We comment on how these local solutions may be used as the building blocks of infinite classes of global solutions glued together with defect branes. Utilising T-duality we find two new classes of AdS3 x S3 x M4 solutions in liB. The first backreacts D5s and KK monopoles on the D1-D5 near horizon. The second is a generalisation of the solutions based on D3-branes wrapping curves in the base of an elliptically fibered CY3 that includes non trivial 3-form flux.